Impact of User-Generated Content on Intentions to Invest in NFTs - Russell Christian; Vieri Luois Cenisius; Muhammad Bagus Darmawan; Juan Carlos Ferrero; Eddy Yansen (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
NFT has many applications which the investors can utilize to invest their assets, for example, in-game assets, educational certificates, and many more. Furthermore, NFT also triggers investors and companies to invest in it because it is a concept related to Intellectual Property, including copyright, trademark, and patent (Bamakan et al., 2022). NFTs have turned online art such as images, paint documents, and more into assets that can be purchased and owned, and creates a value for them and value tends to be unpredictable. NFT (Non-fungible token) is important to study because it is still a new concept, but has provided several advantages for the buyers or investors. Purchasing an NFT would officially grant users ownership over the unique asset, digital art, or collectible. This research intends to identify the correlation between these constructs from the influence of user-generated content. The data samples are collected through random sampling, university students who may have prior or no involvement in NFTs. This study used a qualitative approach to collect the information regarding their behavior in investing in NFT. The questions were separated into four categories based on each of the constructs. The R² value of those constructs is in the range of moderate to weak, and the predictive relevance of the constructs is accurate and significant. This research is but a limited, brief, and small-scale analysis of how user-generated content can have an influence on these driving factors that ultimately lead to the decision of investing in NFTs.